Fatigue crack growth prediction in 2xxx AA with friction stir weld HAZ properties - A. Tzamtzis; A. T. Kermanidis (Fracture and Structural Integrity)
An analytical model is developed to predict fatigue crack propagation rate under mode I loading in 2024 aluminum alloy with FSW HAZ material characteristics. Simulation of the HAZ local properties in parent 2024 AA was performed with overaging using specific heat treatment conditions. The model considers local cyclic hardening behavior in the HAZ to analyze crack growth. For the evaluation of the model, the analytical results have been compared with experimental fatigue crack growth on overaged 2024 alloy simulating material behavior at different positions within the HAZ. The analytical results showed that cyclic hardening at the crack tip can be used successfully with the model to predict FCG in a material at overaged condition associated with a location in the FSW HAZ.